Peningkatan Kompetensi Guru dalam Pembelajaran melalui Supervisi Kelas pada TK PKK Teros Kecamatan Labuhan Haji Semester Ganjil Tahun Pelajaran 2021/2022 - Ruhiyati, Siti (TSAQOFAH, 2021)
The Learning Model is a conceptual and operational learning framework that has names, characteristics, logical sequences, settings and culture. Each learning model chosen must express various realities that are in accordance with the classroom situation and kinds of views of life resulting from the collaboration of teachers and students and are a pattern or certain learning steps that are applied by the teacher so that the goals or competencies of the expected learning outcomes can be quickly achieved. achieved more effectively and efficiently. This school action research activity was carried out at PKK Teros Kindergarten, Labuhan Haji District, Odd Semester for 3 months, starting from July to September 2021 by going through cycle stages. The purpose of this school action research (PTS) is to determine the extent to which the supervision carried out by the principal followed by the provision of guidance/treatment to the target teachers can improve the competence of these teachers in implementing learning strategies in the classroom. In this school action research (PTS) it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase teacher competence by achieving completeness standards. In the first cycle, the increase in teacher competence after classroom supervision was carried out after coaching on the use of several new learning models reached around 33.33% in the second cycle, it could increase to 100%. The results of this school action research show that coaching principals through classroom supervision can improve teacher competence in implementing learning strategies in their respective classes.